Model SOP IT Service Desk Berdasarkan Framework ITIL V3 - Yoppy Mirza Maulana (LPPM POLITEKNIK LP3I BANDUNG, 2022)
IT services are critical to organizational success because of their ability to increase organizational competitiveness and flexibility. In managing quality IT services, IT Service Management (ITSM) is needed. ITSM is the implementation and management of quality IT services to meet business needs. To guarantee and support ITSM, an IT Service Desk (ITSD) function is required. ITSD is a functional unit consisting of a number of staff who are responsible for handling various IT service activities. The function of ITSD is to record and manage and resolve all incidents, problems, IT service requests, and IT service access rights by providing a central point of contact. Therefore, ITSD becomes very important in ensuring and supporting the management of IT services. In carrying out this ITSD function, it is necessary to develop standard operating procedures (SOPs) so that the implementation of work is more structured and measurable. Based on this, the researcher created an ITSD SOP model based on the ITIL V3 framework with a case study in the Pengembangan dan Penerapan Teknologi Informasi (PPTI) section at Universitas Dinamika. This ITSD SOP model produces 3 SOP which includes recording requests and complaints for IT services, analysis and actions, reviewing actions with descriptions of 7 Work Instructions, and 26 Work Records. This ITSD SOP model can serve as a guide in recording, managing, and resolving requests and IT service access management as well as problem-solving both incidents and IT service problems for the organization.